MATURAÇÃO E FECUNDAÇÃO IN VITRO DE OÓCITOS BOVINOS EM TUBOS PREVIAMENTE GASEIFICADOS E MANTIDOS EM BANHO-MARIA - KURTZ FILHO, M.; SILVA, L. M.; MOREIRA, B.; BRUM, D. S.; LEIVAS, F. G.; SILVA, C. A. M.; RUBIN, M. I. B. (Archives of Veterinary Science, 2002)
A produção in vitro (PIV) de embriões bovinos alcançada com vacas de matadouros ou de aspiração folicular in vivo (OPU) é uma prática cada vez mais difundida e a sua simplificação poderia baixar os custos de produção. O objetivo desta pesquisa foi comparar a produção in vitro de embriões em estufa com temperatura, umidade relativa e atmosfera controlada (controle), com tubos de poliestireno gaseificados e mantidos em banho-maria (tratamento). Oócitos obtidos de ovários de vacas abatidas foram maturados in vitro em TCM- 199 modificado com 25mM de N-2-hidroxietilpiperazina-N -2-ácido etanosulfônico (HEPES); 0,025mg/ml de piruvato de sódio, 0,01UI de rFSHh/ml, 0,5µg/ml de LHs e 10% de soro de vaca em estro. Na fecundação in vitro utilizou-se Talp-Fert com 0,06mg/ml de albumina sérica bovina, 0,022mg/ml de piruvato de sódio e 10µg/ml de heparina. O cultivo foi conduzido em placas de 4 poços em SOF com 5% de soro de vaca em estro, 20µl/ml de aminoácidos essenciais e 10µl/ml de aminoácidos não essenciais, sob óleo mineral, em estufa com atmosfera de 5% de CO2, umidade saturada e 39°C, por 9 dias. Na maturação não houve diferença (P>0,05) entre o tratamento e o controle. Porém, a maturação e a fecundação ou somente a fecundação in vitro em tubos mantidos em banho-maria não demonstrou ser uma alternativa recomendada para a produção de embriões bovinos. In vitro maturation and fertilization of bovine oocytes in tubes previously gasified kept in water bath Abstract In vitro bovine embryo production either obtained from oocytes of slaughtered cows or in vivo follicular aspiration (OPU) is a well-known technique and its simplification might reduce the cost of embryo production. The aim of this study was to compare the cleavage rate and embryo development of the in vitro production of bovine embryos using standard culture system (temperature, gas phase and controlled humidity) versus gasified polystyrene tubes kept in water bath. Oocytes obtained from ovaries of slaughtered cows were in vitro maturated in TCM- 199modified with 25 mM of N-2-hidroxyethylpiperazine-N-2-ethanosulfonic acid (HEPES); containing 0.01UI rFSHh/ml and 0.5µg/ml LHs, 0.025mg/ml sodium pyruvate and 10% estrous cow serum. The in vitro fertilization was carried out in Talp-Fert containing 0.06mg/ml BSA, 0.022mg/ml sodium pyruvate and 10µg/ml heparin. The culture was performed in SOF medium with 20µl/ml essential aminoacids, 10µl/ml, non-essential aminoacids and 5% estrous cow serum, with oil overlay, in 4 well dishes and incubated with 5% CO2, maximum humidity at 39°C, for 9 days. The results of this study showed no difference (P>0.05) between the treatment and control groups during the maturation process. However, the maturation and fertilization or only the fertilization in tubes do not represent a viable alternative for the in vitro production of bovine embryos.